2022
DOI: 10.1084/jem.20211403
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of thymic central tolerance by infection with murine roseolovirus induces autoimmune gastritis

Abstract: Infections with herpesviruses, including human roseoloviruses, have been proposed to cause autoimmune disease, but defining a causal relationship and mechanism has been difficult due to the ubiquitous nature of infection and development of autoimmunity long after acute infection. Murine roseolovirus (MRV) is highly related to human roseoloviruses. Herein we show that neonatal MRV infection induced autoimmune gastritis (AIG) in adult mice in the absence of ongoing infection. MRV-induced AIG was dependent on rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 134 publications
1
28
1
Order By: Relevance
“…In addition, several reports have provided important data connecting HHV-6 A/B with other autoimmune diseases, including RA [ 156 ], collagen vascular disease [ 162 ], lupus [ 163 ], connective tissue disease [ 164 , 165 ], Sjögren’s syndrome [ 166 ], systemic sclerosis [ 167 ], thyroid autoimmunity [ 168 , 169 ], severe and acute autoimmune hepatitis [ 187 ], autoimmune hemolytic anemia [ 188 ], and autoimmune neutropenia [ 189 ]. Moreover, in a recent study, Bigley et al [ 197 ] observed that adult mice infected with murine roseolovirus (MRV), which acts like HHV-6 and HHV-7 during the neonatal phase, developed autoimmune gastritis (AIG). It is notable that this autoimmune phenomenon developed months after resolution of acute viral infection.…”
Section: Multiple Tissue Damage and Autoimmunitymentioning
confidence: 99%
“…In addition, several reports have provided important data connecting HHV-6 A/B with other autoimmune diseases, including RA [ 156 ], collagen vascular disease [ 162 ], lupus [ 163 ], connective tissue disease [ 164 , 165 ], Sjögren’s syndrome [ 166 ], systemic sclerosis [ 167 ], thyroid autoimmunity [ 168 , 169 ], severe and acute autoimmune hepatitis [ 187 ], autoimmune hemolytic anemia [ 188 ], and autoimmune neutropenia [ 189 ]. Moreover, in a recent study, Bigley et al [ 197 ] observed that adult mice infected with murine roseolovirus (MRV), which acts like HHV-6 and HHV-7 during the neonatal phase, developed autoimmune gastritis (AIG). It is notable that this autoimmune phenomenon developed months after resolution of acute viral infection.…”
Section: Multiple Tissue Damage and Autoimmunitymentioning
confidence: 99%
“…It may be of interest to recall that HHV-6 transactivates EBV ( 68 ) and that the risk for multiple sclerosis increases when genetically predisposed persons become doubly infected with HHV-6A and EBV ( 69 ). Interestingly, a recent study shows that neonatal infection of mice with a roseolovirus related to HHV-6 may damage the thymus, thus disrupting central tolerance and causing autoimmunity later in life ( 70 ). Future studies may aim at evaluating whether similar dynamics may be operative in AITD.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Bigley et al., a mouse model was infected with murine roseolovirus, which is related to human roseolovirus, and it was hypothesized that murine roseolovirus (MRV) impacted central tolerance by disrupting medullary thymic epithelial cells (mTECs) and CD11c+ thymic dendritic cells (tDCs) in the thymus. The authors were able to determine that neonatal MRV infection leads to a variety of autoantibodies in adult mice ( 92 ). This mechanism of action has not been previously proposed in the context of pemphigus vulgaris development but lends support to extend the investigation into the viral induction of autoimmunity.…”
Section: Findings On Environmental and Lifestyle “Exposome” Factorsmentioning
confidence: 99%